Implementasi Kebijakan Pengembangan Objek Wisata Sei Batu Kelurahan Sei Gohong Kecamatan Bukit Batu Kota Palangka Raya - Apolus Firnandus; Varel Varel; Rendy Stalar (Fakultas Teknik Universitas Cenderawasih, 2026)
This study aims to evaluate the implementation of Palangka Raya City Regional Regulation Number 9 of 2024 concerning Tourism Villages at the Sei Batu tourist attraction in Sei Gohong Village, with a primary focus on facility maintenance and the development of the local community’s creative economy. In addition, this study seeks to understand the extent to which the policy is able to encourage community participation in managing tourism potential in a sustainable manner. The research employs a descriptive qualitative approach through field observations, in-depth interviews, and documentation, with informants purposively selected from management, local government, and community elements. The results indicate that the implementation of the policy has not been optimal, as reflected in weak communication among stakeholders, limited human and financial resources, low commitment among implementers, and ineffective institutional coordination. Furthermore, the lack of regular monitoring and evaluation has also slowed the achievement of policy objectives. This condition has led to neglected tourism facilities and the underdevelopment of local creative economy products as part of community empowerment efforts. These findings indicate a gap between the formulated policy and the reality of its implementation in the field. Therefore, comprehensive improvements are needed in aspects of communication, resources, disposition, and bureaucratic structure, accompanied by enhanced collaboration among relevant stakeholders, so that the objectives of community-based tourism development can be achieved sustainably and provide tangible benefits to the local community